Dual-band Metamaterial Filtenna for WiMAX Application (ELEKTRIKA- Journal of Electrical Engineering, 2019)
Filter and antenna are the most important components in transmission and receiving signal in wireless communication system. The combination of a filter and antenna was known as filtenna. In this paper, a metamaterial band-stop filter is combine with a multiband antenna to produce a dual-band metamaterial filtenna. The purpose of combining both components in one structure is to have a compact size with low transmission line losses. On the other hand, by implementing the metamaterial structure in the filter design, it has increases the overall filtenna performances. All the filtenna designs are been simulated using CST Microwave Studio software.Â  The performances of the dual-band metamaterial filtenna are then analysed based on the S-parameter response and radiation patterns. The simulation results show that the filtenna has operates at 3.6GHz and 5.2GHz, which is mostly suitable for WiMAX application.
Keywords: Filtenna; Dual Band; WiMax; Metamaterial